Positive subsidiarity and its implications for the margin of appreciation doctrine. Issue 3 (September 2019) - Brems, Eva
The article presents an argument in favour of a richer theory of subsidiarity in the European Court of Human Rights context. In particular, the proposal is to include what is called a 'positive' dimension in subsidiarity thinking. That is to say, the article argues that the scholarly and political debate on ECHR subsidiarity has focused mostly on ECHR restraint, associated with a wide margin of appreciation for the States Parties. There is however a complementary dimension in the subsidiarity layout, which concerns the responsibility of national authorities to offer first-line protection of Convention rights. The article examines the role the European Court of Human Rights can play in facilitating that first-line responsibility. The article explores what this means for the margin of appreciation of national authorities.